Oh Mother: The Neglected Impact of School Disruptions - Jaume, David (2019)
Temporary school closures (TSC) represent a major challenge to policymakers across the globe due to their potential impact on instructional time and student achievement. A neglected but equally important question relates to how such closures affect the labor market behavior of parents. This paper provides novel evidence on the effect of temporary school closures on parental labor market behavior, exploiting the prevalence of primary school teacher strikes across time and provinces in Argentina. We find clear evidence that temporary school closures negatively impact the labor market participation of mothers, in particular lower-skilled mothers less attached to the labor force and mothers in dual-income households who face a lower opportunity cost of dropping out of the labor force. This effect translates into a statistically significant and economically meaningful reduction in labor earnings: the average mother whose child is exposed to ten days of TSCs suffers a decline in monthly labor earnings equivalent to 2.92% of the mean. While we do not find any effects among fathers in general, fathers with lower predicted earnings than their spouses also experience negative labor market effects. This suggests that the parental response to TSCs depend, at least in part, on the relative income of each parent. A back-of-the-envelope calculation suggest that the aggregate impact of TSCs on annual parental earnings is more than $113 million, and that the average mother would be willing to forego 1.6 months of labor earnings in order to ensure that there are no TSCs while her child is in primary school.